2011
DOI: 10.5014/ajot.2011.001370
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Sensory Modulation and Social Supports and Health-Related Quality of Life

Abstract: OBJECTIVE. We explored the relationships between sensory modulation and health-related quality of life (HRQOL), social supports, and mental health symptoms of anxiety and depression. METHOD. Twenty-eight adult volunteers ages 18–60 participated in the study. Fourteen adults were sensory overresponsive (SOR), and 14 adults in a matched comparative group were not sensory overresponsive (NSOR). All participants were tested using self-administered measures of sensory processing. RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 20 publications
4
94
0
Order By: Relevance
“…Since sensory reactivity has an impact on everyday life and is associated with higher rates of internalizing symptoms (Kinnealey and Fuiek 1999;Kinnealey et al 2011), it is important to define the sensory phenotype of children with PMS. In our current study, 80 % of children with PMS and 81 % of children with iASD had sensory reactivity abnormalities as evidenced by overall scores on the SSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since sensory reactivity has an impact on everyday life and is associated with higher rates of internalizing symptoms (Kinnealey and Fuiek 1999;Kinnealey et al 2011), it is important to define the sensory phenotype of children with PMS. In our current study, 80 % of children with PMS and 81 % of children with iASD had sensory reactivity abnormalities as evidenced by overall scores on the SSP.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory reactivity in children and adults with ASD has been shown to differ from that of typically developing children (Kientz and Dunn 1997;Ben-Sasson et al 2007;Tomcheck and Dunn 2007;Boyd et al 2010;Crane et al 2009;Dunn et al 2002;Lane et al 2011;Tavassoli et al 2014). Difficulties in sensory reactivity have an impact on everyday life and are associated with higher rates of anxiety (Kinnealey and Fuiek 1999;Kinnealey et al 2011). Sensory reactivity has also been shown to be a heritable trait.…”
Section: Introductionmentioning
confidence: 96%
“…Based on previous studies examining the impact of SPD and sensory over-responsivity in healthy young individuals,92223 adults22232425 and different populations of patients (e.g., children with disabilities or healthy individuals),26272829 we hypothesized that the longer duration of current illness episode and untreated illness together with the higher severity of medications side effects may correlate with specific SPD patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Among typical college students, extreme patterns of sensory processing were strongly associated with distress and difficulty with interpersonal relationships (Ben‐Avi, Almagor, & Engel‐Yeger, ). In a study of adults without a history of a diagnosed mental health condition or trauma, strong sensory overresponsiveness (a construct similar to sensory avoiding and sensory sensitivity) was associated with anxiety and depression, as well as health‐related quality of life (Kinnealey, Koenig, & Smith, ). Other researchers found that overresponsiveness was associated with poor sleep quality, which affects participation and quality of life (Engel‐Yeger & Shochat, ).…”
Section: Discussionmentioning
confidence: 99%